Sugar as nutritional supplement for the zoophytophagous predator Nesidiocoris tenuis - Urbaneja-Bernat, Pablo; Alonso-Valiente, Miquel; Tena, Alejandro; Bolckmans, Karel; Urbaneja, Alberto (2017)
Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) is a zoophytophagous predator widely used in integrated pest management programs in both greenhouse and open-field tomato crops. Mass rearing of N. tenuis is greatly dependent on Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs as food source. Moreover, the addition of this factitious prey after the inoculative releases of N. tenuis under field conditions is recommended to facilitate establishment of this mirid. However, E. kuehniella eggs are expensive and availability is limited. One possible strategy to reduce the amount of E. kuehniella eggs needed is the provision of sugar. In this work, the effect of sucrose as nutritional supplement on selected life-history traits of N. tenuis was studied. The addition of sucrose (0.5 M) ad libitum to a diet of E. kuehniella eggs significantly increased the progeny of N. tenuis and did not affect survival of nymphs nor developmental time. Moreover, addition of sucrose significantly reduced the number of E. kuehniella eggs consumed. These results may have practical implications of interest in mass rearing systems of N. tenuis and its management in fields and greenhouses as a part of biological control programs.